Histological evidence for dermal-endochondral co-ossification of the dorsal blades in the late Paleozoic amphibian Platyhystrix rugosus (Temnospondyli: Dissorophidae). Issue 2 (31st August 2022) - Bowler, Neven; Sumida, Stuart S.; Huttenlocker, Adam K.
ABSTRACT: We provide a detailed histological report of the dorsal blades of the Permo-Carboniferous dissorophid Platyhystrix rugosus . The blades, originally interpreted as hyperelongated neural spines, show compelling histological evidence of a dermal contribution that includes mineralized fibers and plywood-like tissue remarkably similar to extant osteoderm-bearing ceratophryid frogs and trionychid turtles. Their fusion to the vertebrae suggests homology with the osteoderm series of related Permian dissorophids. Although the mode of ossification is difficult to ascertain, both dermal ossification and metaplasia of the surrounding fibrous connective tissue (such as ligaments interconnecting the blades) likely combined to produce the fused blades observed in the closely allied Carboniferous platyhystricine Astreptorhachis . These represent the oldest examples of the phenomenon of dermal-endochondral co-ossification of osteoderms and vertebrae in the postcranial skeleton of a Paleozoic tetrapod. Our findings also highlight the adoption of different developmental mechanisms to produce convergent ecomorphology in sail-backed Paleozoic dissorophid amphibians (dermal blades derived from osteoderms) versus contemporary synapsids (hyperelongated neural spines). Future histological studies should sample additional dissorophid taxa to map the development of osteoderms within a broader phylogenetic context and to better understand their functional diversity.